2010
DOI: 10.1148/radiol.2542090405
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residual Breast Carcinoma Following Neoadjuvant Chemotherapy: Diffusion-weighted Imaging—Comparison with Contrast-enhanced MR Imaging and Pathologic Findings

Abstract: DW MR imaging had at least as good of accuracy as did contrast-enhanced MR imaging for monitoring neoadjuvant chemotherapy. The ADCs prior to chemotherapy did not predict response to chemotherapy. The use of DW imaging to visualize residual breast cancer without the need for contrast medium could be advantageous in women with impaired renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
114
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 35 publications
9
114
0
5
Order By: Relevance
“…This analysis may decrease the number of FN cases. Woodhams et al (16) reported that the accuracy for depicting residual tumors following NAC by DW-MRI is similar to that depicted by contrast material-enhanced MRI. In this study, DW images were referred for the evaluation of tumor response to NAC, however, the final diagnosis of cCR was based on the status of gadolinium enhancement.…”
Section: Discussionmentioning
confidence: 89%
“…This analysis may decrease the number of FN cases. Woodhams et al (16) reported that the accuracy for depicting residual tumors following NAC by DW-MRI is similar to that depicted by contrast material-enhanced MRI. In this study, DW images were referred for the evaluation of tumor response to NAC, however, the final diagnosis of cCR was based on the status of gadolinium enhancement.…”
Section: Discussionmentioning
confidence: 89%
“…3 Previous breast DWI studies employed visual assessment of signal intensities and quantitative analysis of the apparent diŠusion coe‹cient (ADC). [3][4][5][6][7][8][9][10][11][12][13] The signal intensity of breast DWI has been reported useful for diagnosing breast carcinoma. 7,9 In DWI, signal intensity and signal contrast between diŠerent tissues depend on b-value.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] The signal intensity of breast DWI has been reported useful for diagnosing breast carcinoma. 7,9 In DWI, signal intensity and signal contrast between diŠerent tissues depend on b-value. Use of a higher b-value improves image contrast 14 and reduces the fractional contribution of perfusion 1 but yields a lower signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As DWI does not need gadolinium, this method could be advantageous in women with impaired renal function (33).…”
Section: Tumor Persistencementioning
confidence: 99%